2017
DOI: 10.1021/acs.est.7b00328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Major Sources of Atmospheric NH3 in an Urban Environment in Northern China During Wintertime

Abstract: To assess the relative contributions of traffic emission and other potential sources to high levels of atmospheric ammonia (NH) in urban areas in the wintertime, atmospheric NH and related pollutants were measured at an urban site, ∼300 m from a major traffic road, in northern China in November and December 2015. Hourly average NH varied from 0.3 to 10.8 ppb with an average of 2.4 ppb during the campaign. Contrary to the common perspective in literature, traffic emission was demonstrated to be a negligible con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 49 publications
3
59
3
Order By: Relevance
“…Comparable NH3 levels have been measured at multiple stations over the NCP during the winter months Liu et al, 2017a;Zhao et al, 2016), indicating that ammonia-rich conditions are very common. The NHx sources include agriculture, fossil fuel use, and green space, and their contributions vary in different environments Sun et al, 2017;Teng et al, 2017;Pan et al, 2016). We note however that the similar behavior of CO and total NHx does not imply necessarily similar emission sources.…”
Section: Driving Factors For Particle Ph 25mentioning
confidence: 87%
“…Comparable NH3 levels have been measured at multiple stations over the NCP during the winter months Liu et al, 2017a;Zhao et al, 2016), indicating that ammonia-rich conditions are very common. The NHx sources include agriculture, fossil fuel use, and green space, and their contributions vary in different environments Sun et al, 2017;Teng et al, 2017;Pan et al, 2016). We note however that the similar behavior of CO and total NHx does not imply necessarily similar emission sources.…”
Section: Driving Factors For Particle Ph 25mentioning
confidence: 87%
“…To date, there is still no consensus whether nonagricultural emissions are among the major sources of urban atmospheric NH 3 (Felix et al, 2014;Huang et al, 2012;Ianniello et al, 2010;Pan et al, 2016;Teng et al, 2017;Wang et al, 2013), especially in summer season when agricultural sources become more important (Huang et al, 2012). Although uncertainties existed in the current estimation of NH 3 sources, the methods developed here shed light on source apportionment of NH x using stable N isotope under a fractionation scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Geophysical Research: Atmospheres, 123, 5681-5689. https://doi.org/10.1029/2017JD028095 activities, fossil fuel-based emissions may also be an important, even predominant, source of NH 3 in an urban environment, for example, downtown Beijing (Ianniello et al, 2010) and Pittsburgh (Felix et al, 2014). However, a recent study suggested that urban green space and evaporation of deposited NH x (NH 3 + NH 4 + ) on wet surfaces, rather than traffic and agricultural emissions, are the main source for NH 3 in several cities in the North China Plain (NCP; Teng et al, 2017). Hence, there is still considerable uncertainty over NH 3 source types and the magnitude of the NH 3 emissions .…”
Section: Citationmentioning
confidence: 99%
“…For example, Dong et al (2010) (0.14 Tg a −1 ) only estimated NH 3 emitted from the chemical industry. These sources are relatively small compared to agricultural sources of fertilizer application and livestock waste at the national scale; however, recent studies show that fuel combustion, , transportation (Chang et al, 2016;Sun et al, 2017), or local green space (Teng et al, 2017) can be dominant sources of NH 3 in the urban atmosphere.…”
Section: Previous Bottom-up Estimates Of Chinese Nh 3 Emissionsmentioning
confidence: 99%